Hermaphroditism in two populations of Chiton articulatus (Mollusca: Polyplacophora) from the eastern tropical coast of México - Ramírez Álvarez, Citlalith (2014)
Through histological analyses, this study reveals an unusually high incidence of hermaphroditism in Chiton articulatus. Specimens were sampled every 30 days between September 2010 and September 2011 at two locations (Las Brisas and Jaramillo beaches, Acapulco) on the tropical eastern Pacific coast of Mexico. At both sites, hermaphroditism was found throughout the year, although in varying proportions. Higher percentages of hermaphroditism were found during the pre-spawning summer months (Las Brisas Beach 63%, Jaramillo Beach 68%). Two different kinds of hermaphroditic gonads were found, showing a preponderance of either male or female tissues but, commonly, female tissues occupied the greatest part of the gonad cross sections. Similar to other species of polyplacophorans, there was a predominance of males, although M:F sex ratios ranged from 0.7 to 4.5: 1 at Las Brisas Beach and 0.3-8: 1 at Jaramillo Beach.